Dichoropetalum viarium (Apiaceae), a new species from Lorestan Province, Western Iran - Lyskov, Dmitry; Zarre, Shahin; Samigullin, Tahir; Kljuykov, Eugene (Phytotaxa, 2021)
A new species, Dichoropetalum viarium (Apiaceae), is described from the Lorestan Province, Western Iran. The new species differs from D. paucijugum, D. aromaticum, and D. chryseum in the height, shape, diameter, and branching of the stem, shape of the terminal leaf lobes, shape of the bracteoles, shape and size of the mericarps, and shape of the stylopodium. In addition, D. viarium is recognized as a separate species by molecular analysis of nrITS.